Testing the Interface Hypothesis: The evidence from fossilized errors in the use of Turkish case markers - Elena Antonova-Ünlü (Dilbilim Araştırmaları Dergisi)
Sorace & Filiaci (2006) proposed the Interface Hypothesis (IH), according to which interface structures requiring interface between syntax and other cognitive domains are more likely to be vulnerable to incomplete acquisition and fossilization than structures that involve syntactic knowledge only. The aim of this study is to provide a piece of evidence validating or rejecting the IH by investigating the use of case markers in Turkish by native speakers of Russian who are highly proficient speakers of Turkish and have been residing in Turkey for a long period. Fictional narratives are used in the study as the tool for data collection. The findings reveal that the participants demonstrate native-like use of Turkish case markers production of which does not involve external interface. The use of case markers of direct objects, which involves the activation of external interface, is marked with fossilized errors and/or incomplete acquisition in the production of the participants. The findings of the study can be used as a piece of evidence in favor of the IH. Keywords: Interface Hypothesis, case markers, Turkish, native speakers of Russian